2003
DOI: 10.1038/sj.ejcn.1601728
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic differences in dietary habits described by food frequency questions — results from Denmark

Abstract: Objectives: To investigate whether a modest number of food frequency questions are sufficient to describe sociodemographic differences in dietary habits, and to identify sociodemographic characteristics of subjects adhering to food-based dietary guidelines operationalised in a 'healthy-diet index'. Design: Cross-sectional population survey. Subjects: A total of 480 men, 515 women, aged 15-90 y. Random sample of private telephone numbers drawn from regional telephone records, geographically stratified. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
74
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 15 publications
14
74
3
Order By: Relevance
“…The positive association between socioeconomic position and dietary pattern has been confirmed by research carried out on different populations, using different indexes or statistical techniques to determine dietary patterns. As reviewed by Darmon et al (2008), higher values of Healthy Eating Index (Loughley et al, 2004;Angelopoulos et al, 2009;Manios et al, 2009), Diet Quality Index (Patterson et al, 1994;Lallukka et al, 2006), dietary diversity scores (Kant and Graubard, 2007), and other diet-quality measures (Groth et al, 2001;Dynesen et al, 2003;Robinson et al, 2004) have all been associated with a higher socioeconomic position, usually estimated by education level. Using principal components analysis to determine dietary patterns, Robinson et al (2004) found that educational attainment was the most important determinant of a healthy eating pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive association between socioeconomic position and dietary pattern has been confirmed by research carried out on different populations, using different indexes or statistical techniques to determine dietary patterns. As reviewed by Darmon et al (2008), higher values of Healthy Eating Index (Loughley et al, 2004;Angelopoulos et al, 2009;Manios et al, 2009), Diet Quality Index (Patterson et al, 1994;Lallukka et al, 2006), dietary diversity scores (Kant and Graubard, 2007), and other diet-quality measures (Groth et al, 2001;Dynesen et al, 2003;Robinson et al, 2004) have all been associated with a higher socioeconomic position, usually estimated by education level. Using principal components analysis to determine dietary patterns, Robinson et al (2004) found that educational attainment was the most important determinant of a healthy eating pattern.…”
Section: Discussionmentioning
confidence: 99%
“…A healthy dietary pattern has been consistently associated with a higher socioeconomic position (Dynesen et al, 2003;Huot et al, 2004;Robinson et al, 2004;Park et al, 2005;Kant and Graubard, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on socioeconomic differences in vegetable consumption have used different dietary assessment methods, such as food records (Roos et al, 1996;Lynch et al, 1997;Groth et al, 2001;Hulshof et al, 2003), 24 h recalls (Popkin et al, 1996;Lallukka et al, 2001;Giskes et al, 2002;Agudo et al, 2002a) and food frequency questionnaires including varying number of items (Prattala et al, 1992;Smith and Baghurst, 1992;Osler, 1993;Shimakawa et al, 1994;Hjartaker and Lund, 1998;Fraser et al, 2000;Mishra et al, 2002;Perrin et al, 2002;Dynesen et al, 2003). Our data included answers to one frequency question on consumption of fresh vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…The Food Pyramid Index (Massari et al, 2004) and the Global Dietary Index of Food Quality (Huot et al, 2004a, b) focused on food items rich in fat, whereas the Healthy Food Index (HFI) included questions on butter/margarine, vegetables, fruit and coarse bread (Osler et al, 2001), and the Healthy Diet Index (HDI) included questions on vegetables, fruits, meat and fish (Dynesen et al, 2003). The Food Pyramid Index (FPI), HFI and HDI were found to be associated with risk factors, mortality and sociodemographic factors, respectively, but none of the scores has, to our knowledge, been validated against other dietary measures.…”
Section: Discussionmentioning
confidence: 99%